Six-month outcomes of teduglutide treatment in adult patients with short bowel syndrome with chronic intestinal failure: A real-world French observational cohort study. Issue 9 (September 2020) - Joly, F.; Seguy, D.; Nuzzo, A.; Chambrier, C.; Beau, P.; Poullenot, F.; Thibault, R.; Armengol Debeir, L.; Layec, S.; Boehm, V.; Lallemand, J.; Quilliot, D.; et al.
Summary: Background & aims: Teduglutide, a GLP-2-analog, has proven effective in two placebo-controlled studies in reducing parenteral support (PS) in patients with short bowel syndrome-associated intestinal failure (SBS-IF) after 24 weeks. The aim of this study was to describe in a real-life situation the effects of teduglutide treatment and their predictive factors. Methods: We included 54 consecutive SBS-IF patients treated with teduglutide in France for at least 6 months from 10 expert centers. Small bowel length was 62 ± 6 cm and 65% had colon in continuity. PS was 4.4 ±0 .2 infusions per week, started 9.8 ± 1.2 years before. Response (PS reduction ≥ 20%) and PS discontinuation rates were assessed at week 24. Adjusted p values of factors associated with response and weaning were calculated using a multivariate logistic regression model. Results: At week 24, 85% of patients were responders and 24% had been weaned off PS, with a 51% reduction of PS needs and 1.5 ± 0.2 days off PS per week. Response to teduglutide was influenced by a higher baseline oral intake ( p = 0.02). Weaning off PS was influenced by the presence of colon ( p = 0.04), a lower PS volume ( p = 0.03) and a higher oral intake ( p = 0.01). There were no differences based on age, bowel length or SBS-IF causes. Conclusions: Our study confirms the effectiveness of teduglutide in reducing PS needs in SBS-IF patients. We associated reduced parenteral support volume with baseline parenteral volume support, bowel anatomy, and oral intake. These findings underline the role of nutritional optimization when starting the treatment.